Delineating the pro-carcinogenic pathways activated by obesity in Barrett's oesophagus - Casey, Rory (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2011)
Incidences of obesity in the developed world represent a worrying epidemic. Obesity is associated with increased rates of diabetes, cardiovascular disease and cancer. Oesophageal adenocarcinoma rates have increased in the last 25 years hand in hand with obesity, and clear correlations between the two have been demonstrated previously. A major risk factor for oesophageal adenocarcinoma is Barrett's oesophagus, a consequence of prolonged exposure to gastro oesophageal reflux disease (GORD). However, only a fraction of Barrett's patients with GORD will ultimately progress to oesophageal adenocarcinoma indicating that there must be other factors at play in the neoplastic progression of Barrett's oesophagus independent of GORD. The aim of this thesis was to identify pro-carcinogenic pathways activated by obesity in Barrett's oesophagus independent of GORD.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin